Consumer's perceptions and attitudes when seeing product placement in cinema movies - Lenoir, Marine (2009)
I aim at studying the degree of influence that product placements in cinema movies have on consumers’ perceptions and following attitudes. That’s why I would like to determine how consumers are affected by the growing number of product placements into cinema movies and, thereby being able to measure the effectiveness of such marketing strategy.